Determination of the Energy Band Gap and Absorption Coefficient of Thin Films of Chemically Deposited Lead Sulphide, Copper Sulphide and Multilayer Lead Sulphide-Copper Sulphide Thin Films - Iype, Mercy; Varghese, Shaji; Mathew, E.J. (Asian Journal of Chemistry, 2010)
Lead sulphide (PbS) and copper sulphide (CuS) thin films are deposited on glass substrates by chemical bath deposition technique(CBD). Multilayer PbS-CuS thin films are also obtained by chemical bath deposition technique (CBD) by using CuS films as substrates for the deposition of PbS films. These films are annealed in air at different temperatures. Optical studies are separately done on PbS, CuS, and multi layer PbS-CuS films. Optical properties are studied (between 300 nm–900 nm) in a UV-Vis spectrophotometer and the absorbance recorded as a function of photon energy. The optical band gap and maximum absorption coefficient of the deposited and annealed samples are determined. Optical band gap and absorption coefficient decreases with annealing.